ELECTIONS IN THE TURKMENISTAN POWER SYSTEM - KURTOV, Azhdar (CENTRAL ASIA AND THE CAUCASUS, 2006)
The Central Asian countries have failed to grasp the meaning of election campaigns as the central and inalienable element of democracy. The larger part of the region’s ruling elite still looks at elections as an embellishment of authoritarian regimes of all hues. In Central Asia, the question of who will rule in the name of people—the reason why elections are carried out throughout the world—is discussed and settled in high places long before the nation is called to take part in a vote-casting spectacle. Any spectacle requires directors and professional actors, the role of the latter being entrusted to political parties and prominent politicians. For some reason, the skills of the Kazakhstani actors are much higher than elsewhere in the region, therefore elections in Kazakhstan look more plausible. No matter how well orchestrated, the spectacles do flop occasionally. The latest such flop took place in Kyrgyzstan in the spring of 2005. The script supplied by Akaev’s team for the parliamentary election was discarded: the docile Kyrgyz audience was fed up with the old play. All of a sudden, the people climbed up onto the stage and made drastic changes to the script. This is a rare exception. Normally, elections in Central Asia follow the route laid by the communists when the Soviet Union was still alive. All that has changed is that different actors are presenting the same old play with new stage sets. Just as before, the authorities are determining the election results, not vice versa.